Effects of short- and long-term detraining on the metabolic response to endurance exercise - Petibois, C.; Deleris, G. (International Journal of Sports Medicine, 2003)
Changes in the metabolic response to an endurance exercise were studied (18 rowing km at 75 % of maximal aerobic velocity) during detraining in ten rowers previously highly-trained. Maximal aerobic velocity (VO2 max) and the metabolic response to exercise were determined in the 1 st, 24 th, and 47 th week (training), and in the 52 nd, 76 th, and 99 th week (detraining). Over the decrease of VO2 max, detraining induced a biphasic alteration of the previously observed training adaptations: 1-short-term detraining (5 weeks) resulted in a lower adipose tissue triglyceride (TG) delivery during exercise (p = 0.029), but this one did not represent a direct metabolic limit to exercise since the liver TG delivery increased (p = 0.039), allowing that total fatty acid concentration remained unchanged (12.1 +/- 2.4 vs. 11.8 +/- 2.1 mmol/l; weeks 47 vs. 52); 2-long-term detraining (52 weeks) altered even more the metabolic response to exercise with a decreased total fatty acid concentration during exercise (week 99: 10.6 +/- 2.0 mmol/l; p = 0.022), which induced a higher glycolysis utilization. At this moment, a hemolytic response to endurance exercise was observed through haptoglobin and transferrin concentration changes (weeks 47 vs. 99; p = 0.029 and 0.027, respectively), which resulted probably from higher red blood cell destruction. Endurance-trained athletes should avoid detraining periods over a few weeks since alterations of the metabolic adaptations to training may become rapidly chronic after such delays.